Determining priority risk groups for compensation of treatment breaks in radical radiotherapy in patients with locally advanced head and neck cancer - Lohynska, Radka; Jirkovska, Michaela; Novakova-Jiresova, Alena; Kratka, Zuzana; Malinova, Bela (Journal of B.U.ON., 2021)
PURPOSE: Prolongation of radiotherapy worsens the results of treatment of head and neck squamous cell carcinoma (HNSCC). The purpose of this study was to identify the prognostic factors most affected by the prolongation of treatment. METHODS: 184 patients with locally advanced HNSCC were treated with curative chemo-radiation using SIB-IMRT from 2008 to 2016 and the influence of radiotherapy time (RTT) in groups of patients according to prognostic factors was retrospectively evaluated. RESULTS: Median overall survival (OS) was 45 months, median disease-free survival (DFS) was 41 months and median local control (LC) was not reached (mean LRC 68 months). In the multivariate analysis the radiotherapy prolongation negatively affected the LC in stage IV patients, T3/T4, in neck nodes positive disease, in oropharyngeal and oral cavity cancers, after neoadjuvant chemotherapy and in men. The RTT effect on DFS was significant in stage IV patients, patients with neck nodes positive disease and oropharyngeal cancer. RTT prolongation decreased OS within the groups of stage IV and grade 3 tumours. CONCLUSION: Prolonged RTT was associated with worsened OS and LRC, especially in stage IV patients and/or neck node positive disease and/or oropharyngeal cancer and we recommend that these patients should be prioritized in treatment gap compensation in radical radiotherapy for locally advanced HNSCC.
Keywords: senioři; nádory hlavy a krku; senioři nad 80 let; Retrospective Studies; Middle Aged; mužské pohlaví; Head and Neck Neoplasms; Adult; Radiotherapy, Intensity-Modulated; Aged, 80 and over; Neoplasm Staging; ženské pohlaví; retrospektivní studie; Humans; radioterapie s modulovanou intenzitou; lidé středního věku; Risk; riziko; staging nádorů; dospělí; Female; Aged; lidé; Male